2017
DOI: 10.1007/s13300-017-0265-4
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Review of C-Peptide Testing in Diabetes

Abstract: C-peptide is a widely used measure of pancreatic beta cell function. It is produced in equimolar amounts to endogenous insulin but is excreted at a more constant rate over a longer time. Methods of estimation include urinary and unstimulated and stimulated serum sampling. Modern assays detect levels of c-peptide which can be used to guide diabetes diagnosis and management. We explore the evidence behind the various tests available. We recommend the glucagon stimulation c-peptide testing owing to its balance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
274
7
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(307 citation statements)
references
References 70 publications
(89 reference statements)
14
274
7
12
Order By: Relevance
“…Several studies also demonstrated patients with lower c-peptide levels to exhibit an inclination toward insulin, whereas those with higher levels displayed a higher response rate to oral antidiabetics. Therefore, c-peptide may act as a crucial player in the designing of future guidelines related to diagnosis and clinical management of diabetes (12). While planning treatment for patients with T2DM, patient's current glucotoxicity, HbA1c levels, and clinical parameters are important and should be documented.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also demonstrated patients with lower c-peptide levels to exhibit an inclination toward insulin, whereas those with higher levels displayed a higher response rate to oral antidiabetics. Therefore, c-peptide may act as a crucial player in the designing of future guidelines related to diagnosis and clinical management of diabetes (12). While planning treatment for patients with T2DM, patient's current glucotoxicity, HbA1c levels, and clinical parameters are important and should be documented.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, C-peptide levels are associated with diabetes type and duration of disease, specifically a C-peptide level of less than 0.2 ng/ml is associated with a diagnosis of type 1 diabetes mellitus [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, C-peptide can be measured in blood or urine, during a fasting or stimulated sample. We used capillary blood to perform our assay and set the limit of 0,5ng/ml while authors who used urine [11,13,15] set their limit at 0,2 ng/ml to perform their classification. In all cases, it should be taken into account that the presence of large numbers of antiinsulin antibodies that bind both proinsulin and c-peptide can give a falsely high C-peptide reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, insulin therapy is another predictor of worse response to bariatric surgery . In T2DM, insulin is used (ideally) when beta cells fail at an advanced phase of the disease.…”
Section: Predictors Of Long‐term Outcomesmentioning
confidence: 99%